Bringing Psychological Strategies to Robot-Assisted Physiotherapy for Enhanced Treatment Efficacy - Zhong, Bin; Niu, Wenxin; Broadbent, Elizabeth; McDaid, Andrew; Lee, Tatia M. C.; Zhang, Mingming (Frontiers in Neuroscience, 2019)
Abstract—Robotic technologies offer a range of functions to augment clinical rehabilitation practice. However, compliance with robot-assisted rehabilitation techniques has not been optimally achieved. Traditional approaches to improving the treatment efficacy are focusing more on the system function, while psychological factors have not been integrated comprehensively. In this perspective paper, 8 key factors reflecting three conceptions-robot design, function design, and patients’ expectations have been evaluated and analyzed. Clinical results with 28 therapists and 84 patients indicate that integrating psychological strategies into robot-assisted physiotherapy may promote better trust and acceptance of rehabilitation robots.